Pendekatan Spiritual melalui Terapi Dzikir sebagai Alternatif Mengatasi Kecemasan pada Ibu PKK, Desa Galih, Kecamatan Gemuh - Atika Rahmah; Farah Aulia Octaviani; Ayi Romdon Ahmad Fauji; Arini Fauzatannisa; Khairani Zikrinawati (CV. ITTC INDONESIA, 2025)
This Community Service activity was carried out to PKK women in Galih village, Gemuh District, Kendal Regency. This activity aims to minimize the anxiety felt by PKK mothers by providing assistance to psychological conditions. Through this activity, PKK mothers are trained to perform therapy with light tapping, namely the sides of the palms, the base of the eyebrows, the sides of the eyes, under the nose, chin, collarbone, under the armpits, and above the head, while focusing their thoughts on the problems they want to overcome. Interview sessions with PKK mothers were conducted to see the effects and changes after doing Dhikr Therapy. The results of this activity showed that PKK women felt calm by doing Dhikr Therapy. Thus, dhikr therapy is effectively used as an alternative to psychological and spiritual approaches in overcoming anxiety.